Standardizing CRISPR-Cas13 knockdown technique to investigate the role of cdh2 gene in pituitary development through growth hormone expression and transcription factors - Ventura Fernandes, Bianca Helena; Junqueira, Mara S.; MacRae, Calum; Silveira de Carvalho, Luciani R. (Frontiers in Endocrinology, 2024)
Introduction Congenital hypopituitarism (CH) is characterized by the deficiency of pituitary hormones. Among CH patients, 85% lack a molecular diagnosis. Whole Exome Sequencing (WES) identified a homozygous variant (c.865G>A, p.Val289Ile) in the CDH2 gene, responsible for N-Cadherin production, crucial for cell-cell adhesion. Predicted to be likely pathogenic, the variant was found in a patient deficient in GH, TSH, ACTH, and LH/FSH. Its impact on cell adhesion was confirmed in L1 fibroblast cell lines. Objective Create a cdh2 knockdown in zebrafish for investigating its role in pituitary development through growth hormone and transcription factors expression. Methods Utilized pET28B-RfxCas13d-His plasmid for Cas13 mRNA production via in vitro transcription, guiding Cas13 to cdh2 with three RNAs. Injected the complex into single-cell embryos for analysis up to 96 hpf. Assessed gene expression of cdh2, prop1, pit1, and gh1 using RT-qPCR. Evaluated cdh2 protein expression through the western blot technique. Results Knockdown animals displayed developmental delay. The cdh2 expression decreased by 75% within 24 hours, rebounded by 48 hours, and reached wild-type levels by 96 hpf. gh1 expression decreased at 48h but increased by 96 hpf, aligning with WT. No significant differences in prop1 and pit1 expression were observed. Conclusion Our findings underscore cdh2’s role in pituitary development and hormonal regulation, offering insights for developmental biology research.